Sensitivity of Physiological Emotional Measures to Odors Depends on the Product and the Pleasantness Ranges Used - Pichon, Aline M.; Coppin, Géraldine; Cayeux, Isabelle; Porcherot, Christelle; Sander, David; Delplanque, Sylvain (Frontiers in Psychology, 2015)
Emotions are characterized by synchronized changes in several components of an organism. Among them, physiological variations provide energy support for the expression of approach/avoid action tendencies induced by relevant stimuli, while self-reported subjective pleasantness feelings integrate all other emotional components and are plastic. Consequently, emotional responses evoked by odors should be highly differentiated when they are linked to different functions of olfaction (e.g., avoiding environmental hazards). As this differentiation has been observed for contrasted odors (very pleasant or unpleasant), we questioned whether subjective and physiological emotional response indicators could still disentangle subtle affective variations when no clear functional distinction is made (mildly pleasant or unpleasant fragrances). Here, we compared the sensitivity of behavioral and physiological (respiration, skin conductance, facial electromyography (EMG), and heart rate) indicators in differentiating odor-elicited emotions in two situations: when a wide range of odor families was presented (e.g., fruity, animal), covering different functional meanings; or in response to a restricted range of products in one particular family (fragrances). Results show clear differences in physiological indicators to odors that display a wide range of reported pleasantness, but these differences almost entirely vanish when fragrances are used even though their subjective pleasantness still differed. Taken together, these results provide valuable information concerning the ability of classic verbal and psychophysiological measures to investigate subtle differences in emotional reactions to a restricted range of similar olfactory stimuli.